2019
DOI: 10.1590/1519-6984.181476
|View full text |Cite
|
Sign up to set email alerts
|

Volatilization of ammonia in systems of treatment of swine manure with aquatic macrophytes

Abstract: The usage of aquatic plants represents an alternative in the treatment of residues originating from swine. In these systems, one of the N removal methods is the ammonium (NH4 +) uptake and volatilization of ammonia (NH3). In this way, the objective of this work was to evaluate the volatilization rates of NH3 in waste treatment systems swine fluids (SSF) with aquatic macrophytes, as well as the concentration of NH 4+ present in the swine fluids. The experiment was carried out at Campus II/UNOESTE. The treatment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 28 publications
(31 reference statements)
0
2
0
Order By: Relevance
“…Volatilization is favored by high pH and the absence of coverage between the water-atmosphere interface [63]. Pinaffi and Santos [64] showed that the presence of the macrophytes E. crassipes and S. auriculata decreased the volatilization rate, which might explain the better removal observed in the control without macrophytes. The mean concentration of the three replicates and the standard deviation for each physicochemical parameter are presented.…”
Section: Chromium (Iii) Phytoremediation and Tannery Effluent Toxicitymentioning
confidence: 99%
“…Volatilization is favored by high pH and the absence of coverage between the water-atmosphere interface [63]. Pinaffi and Santos [64] showed that the presence of the macrophytes E. crassipes and S. auriculata decreased the volatilization rate, which might explain the better removal observed in the control without macrophytes. The mean concentration of the three replicates and the standard deviation for each physicochemical parameter are presented.…”
Section: Chromium (Iii) Phytoremediation and Tannery Effluent Toxicitymentioning
confidence: 99%
“…Phytoremediation is also a great alternative regarding the use of purifying agents, which is effective in reducing the negative effects of some effluents. This process uses aquatic plants such as macrophytes, which act by removing organic and inorganic pollutants (e.g., salts, metals, pesticides, and petroleum hydrocarbons), or by transforming there into less aggressive compounds (Pio et al, 2010;Pinaffi and Santos, 2019).…”
Section: Introductionmentioning
confidence: 99%